2002
DOI: 10.1073/pnas.172382799
|View full text |Cite
|
Sign up to set email alerts
|

The C2A domain of JFC1 binds to 3′-phosphorylated phosphoinositides and directs plasma membrane association in living cells

Abstract: Phosphatidylinositol 3-kinase products play a central role in the regulation of several intracellular pathways via adaptor proteins that share the ability to bind to 3 -phosphoinositides with high affinity and specificity. JFC1 is a C2 domain-containing protein involved in cellular trafficking that has been shown to bind 3 -phosphoinositides in vitro. In this work, we demonstrate that the C2A domain of JFC1 is the module responsible for its binding to the plasma membrane via 3 -phosphoinositides in vivo. We sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
61
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 38 publications
(54 reference statements)
4
61
1
Order By: Relevance
“…Our quantitative SPR measurements confirm that the C2 domain of PI3K-C2␣ can indeed bind PtdIns(4,5)P 2 and PtdIns(3,4)P 2 ; however, the C2 domain lacks PI specificity and has about 20-fold lower affinity for PtdIns(4,5)P 2 -containing vesicles than the PX domain. The promiscuity and lower affinity of the C2 domain for PIs has been reported for other C2 domains from synaptotagmin I (73), JFC1 (74), and Rsp5p (75). Also, unlike the PX domain, the C2 domain of PI3K-C2␣ is not able to penetrate the lipid monolayer with the packing density comparable with that of cell membranes with or without PI.…”
Section: Discussionmentioning
confidence: 73%
“…Our quantitative SPR measurements confirm that the C2 domain of PI3K-C2␣ can indeed bind PtdIns(4,5)P 2 and PtdIns(3,4)P 2 ; however, the C2 domain lacks PI specificity and has about 20-fold lower affinity for PtdIns(4,5)P 2 -containing vesicles than the PX domain. The promiscuity and lower affinity of the C2 domain for PIs has been reported for other C2 domains from synaptotagmin I (73), JFC1 (74), and Rsp5p (75). Also, unlike the PX domain, the C2 domain of PI3K-C2␣ is not able to penetrate the lipid monolayer with the packing density comparable with that of cell membranes with or without PI.…”
Section: Discussionmentioning
confidence: 73%
“…JFC1 is colocalized with a minor population of azurophilic granules and forms an endogenous complex with Rab27a in neutrophils [46]. The C2A domain of JFC1 expressed in cultured cells is exclusively localized to the plasma membrane, whereas the C2B domain is distributed throughout the cytoplasm [47]. These findings suggests that the C2A domain is responsible for the membrane-binding capacity of JFC1, similar to the case of exophilin4 [29,43].…”
Section: Jfc1/exophilin7/slp1mentioning
confidence: 79%
“…The C2A domain of JFC1 preferentially binds to 3'-phosphorylated phosphoinositides, and most strongly to phosphatidylinositol (3,4,5) triphosphate (PIP 3 ). Although the Ca 2+ effect on the PIP 3 -binding activity in vitro has not directly been investigated, the C2A domain of JFC1 expressed in NIH3T3 cells is dissociated from the plasma membrane after a calcium influx induced by ionomycin [47]. JFC1 is expressed in LNCap prostate carcinoma cells and preferentially colocalizes with prostatic-specific acid phosphatase but rarely with prostate-specific antigen in prostate granules [48].…”
Section: Jfc1/exophilin7/slp1mentioning
confidence: 99%
“…Recently, this technique has been successfully used to identify the phospholipid binding partners of many proteins (Catz et al, 2002;Chiang et al, 2003;Dowler et al, 1999;Gozani et al, 2003). Using this technique, we determined that the three C2 domains of the class I Rab11-FIPs preferentially bound the phospholipids PtdIns(3,4,5)P3 and PA.…”
Section: Discussionmentioning
confidence: 99%
“…Catz and co-workers recently demonstrated that the C2A domain of the tandem C2 domain-containing ATPase JFC1 binds preferentially to PtdIns(3,4,5)P 3 (Catz et al, 2002). JFC1 is a Rab27a effector protein and these authors propose that it positions Rab27a-containing vesicles to a specific docking point on the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%